Additive manufacturing process optimization for complex lattice design architecture - Mazlan, Siti Nur Humaira; Abdul Kadir, Aini Zuhra; Foo, Jin Hoe; Yusof, Yusri (Penerbit UTM Press, 2020)
Among the advanced technology in the manufacturing area, Additive Manufacturing (AM) process has demonstrated its capabilities to produce products with reduced manufacturing time and cost as well as the human interaction (Ashley, 1991). The most significant contribution of this technology is the capability to create almost any shape that could be very difficult to be manufacture. Lattice structures are a lightweight structures and used in a wide range of application ranging from aerospace to the construction industry (Wadley, 2006). Lattice structures consist of continuously repeating unit cells that connect in three dimensions and contain the homogenous structures...